Artificial Intelligence and Legal Reform in Developing Countries: Advancing Ethical, Rights-Based, and Accountable Digital Governance - Hakimi, Musawer; Zarinkhail, Shuaib; Sahnosh, Faqeed Ahmad (Jurnal Ilmiah Telsinas, 2025)
The appreciation and speed of technological development and deployment in artificial intelligence (AI) bring enormous risks and opportunities to the developing world. Developing countries are likely to have less vested systems of regulation which risk ethical liability, legal liability, and social inclusion. This article presents an interdisciplinary legal framework for AI regulation for developing countries for the responsible deployment of AI vis-a-vis innovation relative to fundamental human rights and ethical safeguards. Using a huge trove of scholarly articles, policy documents, and case studies dating from 2017 to 2025 from journals such as Springer, IEEE Access, Wiley, MDPI, and ACM, this research synthesizes interdisciplinary lessons in computer science, law, ethics, and social sciences. The review of the troves of data highlighted important aspects of regulation, risk management, and governance principles towards AI regulations in emerging economies. The model proposed in this paper includes a mandatory assessment process for AI, deal with standards for algorithmic explain ability, autonomous regulatory agencies, sectoral risks, principle of inclusive design, public education in digital literacy, and strong protections for human rights. Developing countries require a rights-based, multi-stakeholder regulatory approach that addresses the technical, ethical, and legal complexities of AI. Implementing such a framework will promote equitable AI innovation while safeguarding human rights and fostering sustainable development.